Structuring Free-Standing Foils for Laser-Driven Particle Acceleration Experiments - Gheorghiu, Cristina C.; Ionescu, Stefania C.; Ghenuche, Petru; Cernaianu, Mihail O.; Doria, Domenico; Popa, Daniel; Leca, Victor (Frontiers in Physics, 2021)
The recent development of petawatt-class laser systems sets a focus on the development of ultra-thin free-standing targets to access enhanced particle acceleration schemes vital for future applications, such as, e.g., medical and laser-driven nuclear physics. Specific strategies are required to improve the laser-to-particle energy conversion efficiency and increase the maximum particle energy. One of the promising approaches is based on the target design optimization; either by tuning key parameters which will strongly affect the laser-matter interaction process (e.g., material, composition, density, thickness, lateral dimensions, shape) or by using micro/nano-structures on the target surface. At ELI-NP, considerable efforts are dedicated to extend the target capabilities beyond simple planar target design and develop complex targets with tailored properties suitable for high-power laser-plasma interaction experiments, as well as for studies with gamma and positrons beams. The paper provides an overview of the manufacturing capabilities currently available within ELI-NP Targets Laboratory for providing users with certain types of solid targets, specifically micro/nanostructured gold and copper foils and microns thick, porous anodized alumina. Also, optimization studies of alternative patterns (micro/nano dots) on silicon substrate are presented for future implementation on metallic free-standing thin foils.